Stress in Written and Sight Translation in Training Setting - Baghi, Hoorieh; Khoshsaligheh, Masood (Hikma, 2019)
Stress can have facilitative or debilitative impacts on human performance, including translation. To investigate stress in translation, a sample of translation students were asked to complete a written and a sight translation task from English to Persian. The changes in their blood pressure and heart rates were measured before and during the translation tasks. The findings revealed that sight translation is significantly more stressful than written translation and can result in a meaningful rise in blood pressure and heart rate. A significant increase in heart rate was observed during the written translation. Comparing the significant changes in systolic blood pressure of the male participants and heart rate of the female participants during the written translation, with no significant difference between the blood pressure and heart rate of both male and female participants throughout the sight translation, showed the difference in the stress response between the genders disappears during excessive stress.